Competencies for fresh graduates' success at work: Perspectives of employers. Issue 1 (February 2019) - Pang, Elvy; Wong, Michael; Leung, C. H.; Coombes, John
This article investigates Hong Kong employers' views on graduate competencies that facilitate new graduates' success in the workplace. The methodology involves the use of a questionnaire to elicit responses from business employers on the importance of specific competencies contributing to the success of fresh graduates at work. The findings indicate that all of the competencies examined are important to a degree. 'Ability and willingness to learn', 'teamwork and cooperation', 'hardworking and willingness to take on extra work', 'self-control' and 'analytical thinking' are the five highest-ranking competencies measured, although all are clearly necessary for success. Hard and soft skills are rated equally important by employers overall. Recommendations for developing competencies among university students prior to their entry to the workforce are discussed. As the competencies are of a practical nature, it is suggested that universities work together with industry to develop workplace-oriented programmes. This is the first research, to the authors' knowledge, that approaches desirable graduate competencies from the perspective of the skills gap in the context of Hong Kong.